Solitary fibrous tumour of palate, case report - Martínez-Martínez, Enrique Antonio; Meza-Garcia, Gerardo; Cano-Valdez, Ana Maria; Dominguez-Malagon, Hugo (Journal of Oral Diagnosis, 2023)
Solitary fibrous tumour (SFT) is a spindle-cell mesenchymal neoplasm, has been reported in various locations but the oral cavity is a distinctly uncommon region. Case report: a female patient, 30 years old with a painful tumour the lesion measured approximately 4 cm; computed tomography showed a heterogeneous large mass in palate extending to oral cavity preserving osseous tissue; an incisional biopsy was performed; histopathological examination demonstrated a circumscribed lesion composed mainly of hyalinized fibrous connective tissue with intermittent paucicellular and hypercellular areas and a hemangiopericytoma-like vasculature were noted. Immunohistochemically: were strongly positive for CD34, bcl-2 and vimentin but negative for S-100 protein, calponin, CD-99. CD-21, CD-23, CD-35, Fascin and EMA; a diagnosis of solitary fibrous tumor was made. The tumour was treated by complete surgical excision; no recurrence was noted at a 15year follow-up.